Open science publishing practices can break commercial publishers’ dominant position in the dissemination of scientific results - Braak, Pascal (Dutch Journal of Applied Linguistics, 2024)
In this response to Diamond is a scientist’s best friend, Pascal Braak discusses open science practices from a bibliographic perspective and among other things, sketches how a fully open and transparent knowledge generation process may break the power of commercial publishers.